GIANT OVARIAN CYST-AN UNUSUAL FINDING - Mehboob, Mukhtar; Naz, Samina; Zubair, Muhammad; Kasi, Muhammad Ashraf (Journal of Ayub Medical College Abbottabad, 2014)
A 16 year old unmarried girl presented with complaints of abdominal distension, vomiting, constipation, difficulty in breathing and restlessness. On examination abdomen was grossly distended with fluid thrill. Ultrasonographic examination revealed that there was a huge cystic collection with internal debris, multiple septations involving the whole abdomen and pelvis originating from right ovary. The left ovary was normal. Her laparatomy was done. A giant ovarian cyst measuring 45Ã—32Ã—28 cm, which weighed18 Kg(almost 1/3 of whole body weight), was removed as such like a yoyo balloon. Post-operative recovery was smooth. Histopathological examination revealed that it was mucinous cystadenoma. Keywords: Giant, ovarian cyst, Mucinous cystadenoma, ovary